Description of the larva of Meliboeus morawitzi (Semenov, 1905 (Coleoptera: Buprestidae) - Prokhorov, Alexey V.; Gubin, Oleksandr I. (Zootaxa, 2019)
The mature larva of Meliboeus morawitzi (Semenov, 1905) from material collected within the roots of Artemisia marschalliana Spreng. in Khomutovskyi Steppe Nature Reserve (Donetsk Region, Ukraine) is described. Diagnosis of the larva of this species together with improved key to the known larvae of the genus Meliboeus are provided.